2014
DOI: 10.1177/1359105314554818
|View full text |Cite
|
Sign up to set email alerts
|

Perceived control and self-efficacy, subjective well-being and lifestyle behaviours in young Iranian women

Abstract: This study examined whether young Iranian women's perceived control and self-efficacy, as a component of cognitive social capital, predicts health and well-being. A total of 391 women aged between 18 and 35 years completed a survey including scales measuring control and self-efficacy and health outcomes including quality of life, satisfaction with life and lifestyle behaviours. Statistical analyses indicated that participants had low perceived control and influence over community affairs together with high per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 24 publications
3
38
2
1
Order By: Relevance
“…Effort, work, ambition and perfectionism correlate positively with perception of wellbeing (Bláz-quez-Garcés et al, 2014;Hampson & Friedman, 2008), mainly self-acceptance, personal growth and purpose in life. As indicated in other studies (Esnaola & Revuelta, 2009;, participation in activities requiring effort, like physical exercise, offers people the chance to develop individual characteristics that help them to become more perseverant, dynamic and stable, especially in the case of women (Courneya et al, 2012;Salehi, Harris, Coyne, & Sebar, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Effort, work, ambition and perfectionism correlate positively with perception of wellbeing (Bláz-quez-Garcés et al, 2014;Hampson & Friedman, 2008), mainly self-acceptance, personal growth and purpose in life. As indicated in other studies (Esnaola & Revuelta, 2009;, participation in activities requiring effort, like physical exercise, offers people the chance to develop individual characteristics that help them to become more perseverant, dynamic and stable, especially in the case of women (Courneya et al, 2012;Salehi, Harris, Coyne, & Sebar, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of the studies described in this review focus on human functioning in terms of performance and behaviour; the link between self-efficacy and wellbeing is much less extensively researched. Yet, there are ample examples from varying disciplines and a range of participant samples: self-efficacy has found to be positively related to wellbeing among adolescents (Caprara et al 2006), people who regularly exercise (Briki 2018), South African marginalised youth (Melato et al 2017), cancer patients in the UK (Foster et al 2016), new mothers in Israel (Kestler-Peleg, Hamama-Raz, and Osnat 2016), and among young Iranian women (Salehi et al 2016). Benight and Bandura (2004) conducted a review of studies investigating the role of self-efficacy in recovery from various types of trauma, including natural disasters, technological catastrophes, terrorist attacks, war, and assaults, and found that self-efficacy was positively related to trauma recovery in all studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, participants attending the targeted intervention at their GP had lower baseline self-efficacy than those who received the digital personal health profile alone [ 28 ]. This may have influenced the results as self-efficacy is known to be associated with well-being [ 43 ].…”
Section: Discussionmentioning
confidence: 99%